Acute volvulus of the stomach - Castiglioni, Juan C; Estapé, Gonzalo; Bergalli, Luis E; Camaño, Mario C; Ituño, Carlos (Cirugía del Uruguay, 1972)
Two cases of acute, stomach volvulus give rise to a brief presentation of the pathological and clinical aspects of this disease.